MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA KELAS IV MELALUI MEDIA KARTU BERPASANGAN MATERI KOSA KATA BARU DI SD NEGERI 5 PALEMBANG - Rahma Kurnia; Rahmi Susanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to improve Indonesian language learning outcomes using paired cards as a medium for class IV students at SD Negeri 5 Palembang, totaling 22 students consisting of 14 boys and 8 girls. This type of research uses classroom action research by collecting data through tests, observation and documentation. This data analysis technique uses data analysis with an interactive model where data collection is carried out using 2 cycles, namely cycle I and cycle II. The results of this research indicate that the use of paired card media in learning new vocabulary material can help improve the learning outcomes of class IV students at SD Negeri 5 Palembang. The increase in learning outcomes can be seen from the learning outcomes that have gone through the Pre-cycle, cycle I and cycle II stages. Using paired card media in learning shows an increase in student learning outcomes as shown by an increase in the Pre-cycle, only 7 students completed it, 10 students completed the first cycle, and in the Second Cycle there was an increase with 18 students achieving completion. Thus, it can also be seen from the percentage of completeness of students, namely in the pre-cycle stage the percentage of completeness was 31.81%, in Cycle I 45.45% and the percentage of completeness increased to 81.81%, in cycle II, so it can be concluded that the paired card learning media can improve results. student learning.